Faktor yang Mempengaruhi Kondisi Financial Distress Perusahaan Property dan Real Estate - Siti Aisyah Nasution (Owner : Riset dan Jurnal Akuntansi, 2019)
The purpose of this study was to find out the influence of Financial Ratio on financial distress in Property and Real Estate companies listed in the Indonesian Stock Exchange. The factors which tested in this research were Current Ratio. Leverage Ratio, and Cash Flow. The study used causal method which was aimed to analyze the influence of independent variables on dependent variable. The population was 22 property and real estate companies listed in the Indonesian Stock Exchange in the period of 2011-2014 until there were 88 saturated samples. The data were analyzed by using logistic regression analysis. The result of the study showed that the data in this study were in accordance with the model and the result of the matching test of regression model which was able to analyze the problems. Simultaneously, the result of Ominbus Test of Model Coefficient showed that Current Ratio, Leverage Ratio and Cash Flow had significant influence on financial distress. Partially, Current Ratio, and Cash Flow had positive and significant influence on Financial Distress, Leverage Ration had negative but significant influence on Financial Distress.